2017
DOI: 10.1039/c7ta07186h
|View full text |Cite
|
Sign up to set email alerts
|

Heteroatom functionalized activated porous biocarbons and their excellent performance for CO2 capture at high pressure

Abstract: Activated biocarbons with a porous structure and nitrogen functionalities are synthesized from the prolific waste biomass, Arundo donax, and an organic material, chitosan, by a simple one step chemical activation with ZnCl2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 56 publications
(44 reference statements)
1
49
0
Order By: Relevance
“…The capacity of CO 2 capture at 298 K at 1 bar for the samples was found to follow this order: AC (3.15 mmol/g) > NAC-2 (2.75 mmol/g) > NAC-1 (2.69 mmol/g) > NAC-3 (2.44 mmol/g) > NAC-4 (1.95 mmol/g). 43,44 But in this work, it did not play a dominant role. We can reach the conclusion that the specific surface area has the most significant effect on the capacity of CO 2 capture.…”
Section: Raman Spectroscopy Analysismentioning
confidence: 76%
See 1 more Smart Citation
“…The capacity of CO 2 capture at 298 K at 1 bar for the samples was found to follow this order: AC (3.15 mmol/g) > NAC-2 (2.75 mmol/g) > NAC-1 (2.69 mmol/g) > NAC-3 (2.44 mmol/g) > NAC-4 (1.95 mmol/g). 43,44 But in this work, it did not play a dominant role. We can reach the conclusion that the specific surface area has the most significant effect on the capacity of CO 2 capture.…”
Section: Raman Spectroscopy Analysismentioning
confidence: 76%
“…-Besides, nitrogen-containing functional groups were reported to have a positive impact on CO 2 capture. 43,44 But in this work, it did not play a dominant role. AC has the lowest nitrogen content and highest specific surface area, while its capacity of CO 2 capture was the best among the samples.…”
Section: Raman Spectroscopy Analysismentioning
confidence: 76%
“…The Q st value is an important measure of the interaction strength between the CO 2 molecule and the carbon surface. The initial Q st at low CO 2 coverage is in the range of 24.0‐30.4 kJ mol −1 , comparable to the reported results of nitrogen doped carbons ,. Agar‐0.75‐600‐1 has the highest value of 30.4 kJ mol −1 , which might be an interplay between the nitrogen content and pore size: although more pores larger than 1 nm are formed, but more nitrogen is doped into the carbon with more urea addition.…”
Section: Resultsmentioning
confidence: 95%
“…This indicated that the pore structure and N‐doping of the N‐HPC‐800 also influenced the high‐pressure CO 2 adsorption capacity. As demonstrated in previous reports, super‐micropores or small mesopores (below 2–3 nm) govern the sorption behavior at a high pressure, and basic functional groups by N‐doping are favorable for the adsorption of acidic CO 2 molecules . We compared the performances of our N‐HPC‐800 to representative porous carbon materials as CO 2 high‐pressure solid adsorbents.…”
Section: Resultsmentioning
confidence: 99%